REFORMING THE EDUCATION SYSTEM IN THE CONDITIONS OF A NEW STAGE OF DEVELOPMENT - Hakimovich, Hakimov Nazar; Karimovich, Sadikov Anvar; Abdulajanovich, Abdumalikov Abdulatif; Begijonovich, Iminov Begzod (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the authors investigated the system of preschool and school, secondary special education of the Republic of Uzbekistan. The authors consider the issues of educational reform in the context of deepening democratic reforms in the context of a new stage in the country’s development. The article explores current issues of improving the work of educational institutions. An attempt has been made to study the current state of preschool institutions, secondary schools and the most important strategic tasks facing it, which directly affect the methods, content, and also the creation of an intellectual environment for students. Based on a scientific analysis and a critical assessment of the state of education, the most relevant trends in its development are considered as an important factor in the upbringing of a harmoniously developed generation in a new stage of development.